DIALOGIC ENGAGEMENT AND ENGLISH LANGUAGE PROFICIENCY: AN EXPLORATION - Eustaquio, Sweetie Joy Inocencio (President University, 2024)
This study investigates the dialogic engagement and English language proficiency in theselected municipalities in Capiz Division during the academic year 2023-2024. The researcheruutilized descriptive correlational research using researcher-made questionnaire that wascarried out with a sample population of 332 from the total of 473 teachers that use Englishlanguage as a medium of instruction. Stratified random sampling was employed to determinethe number of respondents per school. Statistical tools used were frequency count, percentage,mean, T-test, ANNOVA and Spearman rank correlation analysis. The study conducted in theProvince of Capiz unveiled a notably high level of dialogic engagement among teachers acrossvarious contexts, including household interactions, school dynamics, and communityinvolvement. This emphasizes a conducive environment for collaborative networks andcontinuous learning, echoing the importance of dialogic interdependence as an enabler foreffective leadership. Additionally, the findings regarding teachers' English languageproficiency showcased a high level of proficiency, particularly evident in expressive abilities,comprehension skills, and overall confidence in language use. This aligns with the emphasison communication skills and strategic aptitude as essential components of effective leadership.Moreover, while no significant variance was observed in the overall English languageproficiency levels concerning various teacher profiles, a significant gender differenceemerged. Female teachers demonstrated notably higher proficiency in English compared totheir male counterparts, highlighting a potential area for targeted intervention to addresscompetency barriers. The significant correlation identified between the extent of dialogicengagement and the level of English language proficiency underscores the importance ofeffective communication and collaboration skills in enhancing language proficiency, essentialattributes for effective leadership development among educators in Capiz. The study providespractical insights for educators to enhance language instruction by understanding therelationship between dialogic engagement and English Language Proficiency fostering moreeffective teaching method. Findings contribute to the design of targeted professionaldevelopment programs educators, focusing on dialogic engagement strategies, therebyelevating the language proficiency of educators in English as a medium of instructions.